Increased efficiency in the second-hand tire trade provides opportunity for dengue control. (21st January 2018) - Pliego Pliego, Emilene; Velázquez-Castro, Jorge; Eichhorn, Markus P.; Fraguela Collar, Andrés
Highlights: A model to assess the importance of tire transportation in Dengue outbreaks is proposed. Persistent dengue states can be induced due to tire trade, regardless of whether favorable environmental conditions are met for an outbreak. The proposed model suggests that tire-trade regulation may be beneficial in reducing the Dengue spread. Particular regulation strategies for the trade in second-hand tires play an important role in the control of the disease. Abstract: Dengue fever is increasing in geographical range, spread by invasion of its vector mosquitoes. The trade in second-hand tires has been implicated as a factor in this process because they act as mobile reservoirs of mosquito eggs and larvae. Regional transportation of tires can create linkages between rural areas with dengue and disease-free urban areas, potentially giving rise to outbreaks even in areas with strong local control measures. In this work we sought to model the dynamics of mosquito transportation via the tire trade, in particular to predict its role in causing unexpected dengue outbreaks through vertical transmission of the virus across generations of mosquitoes. We also aimed to identify strategies for regulating the trade in second-hand tires, improving disease control. We created a mathematical model which captures the dynamics of dengue between rural and urban areas, taking into account the movement and storage time of tires, and mosquito diapause. We simulate a series of scenarios in which a mosquito population is introduced to a dengue-free area via movement of tires, either as single or multiple events, increasing the likelihood of a dengue outbreak. A persistent disease state can be induced regardless of whether urban conditions for an outbreak are met, and an existing endemic state can be enhanced by vector input. Finally we assess the potential for regulation of tire processing as a means of reducing the transmission of dengue fever using a specific case study from Puerto Rico. Our work demonstrates the importance of the second-hand tire trade in modulating the spread of dengue fever across regions, in particular its role in introducing dengue to disease-free areas. We propose that reduction of tire storage time and control of their movement can play a crucial role in containing dengue outbreaks.